2003
DOI: 10.1016/s0928-7655(03)00045-9
|View full text |Cite
|
Sign up to set email alerts
|

International benchmarking of electricity distribution utilities

Abstract: Benchmarking by means of applying the DEA model is appearing as an interesting alternative for regulators under the new regimes for electricity distributors. A sample of large electricity distribution utilities from Denmark, Finland, Norway, Sweden and the Netherlands for the year 1997 is studied by assuming a common production frontier for all countries. The peers supporting the benchmark frontier are from all countries. New indexes describing cross country connections between peers and their i nefficient uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Mukherjee presented several DEA models for analysis of used energy efficiency in US manufacturing firms (Mukherjee 2008). DEA has been also used for benchmarking the electric utilities in Europe and northern Europe (Jamasb, Pollitt 2003;Edvardsen, Førsund 2003).…”
Section: Energy Efficiency and Dea: A Literature Reviewmentioning
confidence: 99%
“…Mukherjee presented several DEA models for analysis of used energy efficiency in US manufacturing firms (Mukherjee 2008). DEA has been also used for benchmarking the electric utilities in Europe and northern Europe (Jamasb, Pollitt 2003;Edvardsen, Førsund 2003).…”
Section: Energy Efficiency and Dea: A Literature Reviewmentioning
confidence: 99%
“…Other studies also offering insightful discussions on the use of DEA to inter-country benchmarking of electricity distribution utilities include Pardina et al (1998), Edvardsen and Førsund (2003), Jamasb and Pollitt (2003), and Estache et al (2004).…”
Section: Inter-country Studiesmentioning
confidence: 99%
“…Study DMUs Inputs Outputs Environmental Variables Edvardsen and Førsund (2003) 122 distribution utilities from Denmark, Finland, Norway, Sweden and Netherlands.…”
Section: Modelmentioning
confidence: 99%
“…According to Zhou et al [24], 38% of the studies dealing with energy and environment (E&E) issues are focused on electricity industry. Moreover, they found that, prior to 1990, the relevant literature had mainly focused on the electricity generation plants (see Färe et al [26,27]), whereas the focus was placed on the efficiency of electricity distribution utilities after 1990 (see Edvardsen et al [28]; Forsund, Kittelsen [29]). Modeling the environmental performance has widely attracted the attention of researchers, and about 25% of E&E studies that were carried out from 1990 to 2008 focused on this area (see Färe et al [30]).…”
Section: Introductionmentioning
confidence: 99%